Effect of Romifidine injection on clinical indicators, biochemical and hematological parameters in camels - Al-Lazkani, Rahaf; Al-Omari, Azzam (Journal of agricultural, environmental and veterinary sciences, 2023)
Romifidine was injected intravenously at a dose of (40 μg/kg) in six camels whose ages ranged between (3-4.5) years, and weighed approximately between (400-300) kg, in order to study the effect of this analgesic on some clinical indicators (heart rate). And the rate of breathing movements, body temperature, and rumen movements), and some parameters of cellular blood components (white blood cells, red blood cells, hemoglobin, blood stacks, and platelets), as well as some biochemical parameters (glucose, creatinine, sodium, potassium, chlorine, Alanine transaminase (ALT) and Aspartate Aminotransferase (AST) enzyme). Where blood samples were taken before the injection and 15-30-60-120 minutes and 24 hours after the injection.The results of Romifidine injections in camels showed a decrease in heart rate and breathing movements after the injection at (30-120) minutes (P≤0.05), and there was a significant increase in body temperature (P≤0.05) per minute (30-60) After the injection, as for the rumen movements, a significant decrease was observed in the minute (30-90).As for the criteria of cellular blood components, a significant increase was observed in the number of white blood cells per minute (120) after the injection (P≤0.05), while no significant change was observed in the blood platelets (P≤0.05). Significant decrease in it (60) minutes after injection (P≤0.05).As for the biochemical parameters, a significant increase in blood glucose was observed from (15) minutes to (24) hours after the injection (P≤0.05), and an insignificant increase (P≤0.05) in the sodium and chlorine ions after (15-30) minutes of the injection. No significant change was observed in potassium and creatinine (P≤0.05), as for AST, and ALT enzyme activity, a significant increase was observed (24) hours after injection (P≤0.05).
Keywords: Camel; Romifidine; Haematological Parameters; Biochemical